Phenotypic and genotypic characterisation of two closely related subgroups of Candida rugosa in the clinical specimens - Tay, S.T.; Tan, H.W.; Na, S.L.; Lim, S.L. (Microbiology Society, 2011)
In this study, six clinical isolates (two from blood, two from urine, and one each from bronchoalveolar lavage and vaginal swab) were identified as Candida rugosa based on carbohydrate assimilation profiles by API 20C AUX and ID32 kits. Sequence analysis of the D1/D2 domain of the yeasts differentiated the isolates into two subgroups, A and B (three isolates per subgroup) which are closely related (99.1-99.6% similarity) to C. rugosa ATCC 10571 strain. Comparing to C. rugosa type strain, the ITS sequence similarity for subgroup A is only 89.2% (29 mismatches and 1 deletion) and for subgroup B, 93.7% (20 mismatches). All isolates grew green colonies on the Oxoid Chromogenic CANDIDA agar, with darker pigmentation observed for subgroup A. All isolates were able to grow at 25-42 degrees C, but not 45 degrees C. The isolates had identical enzymatic profiles as determined by API ZYM analysis and produced proteinase. High amphotericin MICs (greater than or equal to 1 microgram/ml) were noted for two isolates from each subgroup. Dose-dependent susceptibility to fluconazole (MIC, 32 micrograms/ml) was noted in a blood isolate. The biofilms of the isolates demonstrated increased resistance to amphotericin and fluconazole. The greater ITS sequence variability of the subgroup A is in support of the yeast to be recognised as a distinct species; however, further verification using more sophisticated molecular approaches is required. Sequence comparison study suggests the association of subgroup A with environmental sources and subgroup B with clinical sources. Accurate identification and antifungal susceptibility testing of C. rugosa are important in view of its decreased susceptibility against amphotericin and fluconazole. The ITS region has been shown to be a valuable region for differentiation of closely related subgroups of C. rugosa.